A 41-Year-Old-Man With Diffuse Axonal Injury: A Case Report - Rayhan Al-ghifari Iridansyah Siregar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Diffuse axonal injury (DAI) is a significant pathological feature of traumatic brain injury (TBI) and poses a considerable challenge in clinical neurology. This injury is characterized by microscopic damage to axons in neuronal tracts, especially within the corpus callosum and brainstem, leading to severe outcomes, including high morbidity and mortality. We report a case involving a 41-year-old male who presented to the emergency room of RT Hospital after a motorcycle accident, resulting in a prolonged loss of consciousness lasting over 12 days. The diagnosis of DAI was confirmed through detailed history taking, thorough physical and neurological examinations, and MRI brain imaging, which revealed characteristic axonal damage. This case underscores the prevalence of DAI among motorcycle accident victims, regardless of age, and the typical presentation of prolonged unconsciousness. The patient was treated with an intensive regimen aimed at reducing injury effects and promoting neurological recovery. This included mannitol to lower intracranial pressure, nimodipine for neuroprotection, and phenytoin to prevent seizures. Additionally, amantadine and alinamin F were used to enhance cognitive recovery. Supportive therapies comprised paracetamol for fever, ceftriaxone and levofloxacin as antibiotics, and pantoprazole for gastrointestinal protection. Despite these comprehensive efforts, the prognosis remains poor, with a high risk of lasting neurological deficits. This case highlights the critical implications of DAI in TBI management and underscores the need for early diagnosis and ongoing research to better understand and treat this severe condition.